The content of coliform and Escherichia coli on Goat Meat From Traditional Markets In Bandar Lampung - N Riffiandi; G G Maradon; V R Pertiwi (Politeknik Negeri Lampung, 2021)
Meat is an animal product which is a source of protein for human life. The research aimed to determine of contamination of coliform and E. coli in Goat Meet from traditional market in Bandar Lampung. Survei method used in this research and the data were analized descriptively. Sample was taken from 5 traditional market in Bandar Lampung (Pasar Koga, Pasar Bambu Kuning, Pasar Way Kandis, Pasar Tamin dan Pasar Tugu) each 250 gr. Sample was analized in Lampung Veterinary Center Laboratory. The lowest contamination of coliform got from Pasar Bambu Kuning with <3,6 MPN/gr and the highest got from Pasar Tugu and Pasar Tamin with 1100 MPN/gr. Therefore, contamination of E. coli from all markets is <101. The result showed all meat in traditional market indicated contamination of Coliform and Escherichia coli.